Developing Pocket Book of Laboratory Safety for Students in SMA Negeri 1 Taman - Safitri, Lailis (Proceeding International Conference on Science and Engineering, 2019)
This works describes a study of developing pocket book of laboratory safety in SMA Negeri 1 Taman. Developing of the pocket book is to increase the awareness of laboratory users (students and teachers) and minimize the work accidents in the laboratory. Based on the observation of the researchers only 38.2% of users in the laboratory have awareness of laboratory safety. The Pocket book was developed using 4-D model that modified to 3-D. The result of the validity is 80,0% which indicates that the pocket book deserves to be used. And the students responses is 87,5% which shows that the students are very enthusiastic.